Pendampingan Pemanfaatan E-Commerce Untuk Pemasaran Songket Dan Kerupuk Di Desa Burai Sumatera Selatan - Purbiyanti, Erni; Sari, Yulia; Putri, Nurillla Elysa; Yunita, Yunita; Ritonga, Utan Sahiro; Sulastri, Merna Ayu; Huanza, M (Pakis Journal Institute, 2024)
The adoption of information technology, particularly e-commerce, is a strategic solution to address marketing challenges in the digital transformation era. In Burai Village, e-commerce implementation remains limited, necessitating assistance to empower the community in utilizing e-commerce for marketing and enhancing entrepreneurial capacity. The program began with a needs assessment, analyzing community requirements and potentials, followed by resource and budget planning. Implementation involved the community in creating online stores, optimizing promotional features like live streaming, managing inventory, and generating shipping labels. The program concluded with an evaluation phase. Results showed increased e-commerce knowledge among the community, a higher number of e-commerce account owners, and improved skills in using platform features. Surveys revealed high community satisfaction with e-commerce sales features and recognition of its pivotal role in boosting product sales. This initiative underscores the importance of targeted assistance in fostering digital marketing capabilities within rural communities.